1993
DOI: 10.1523/jneurosci.13-04-01624.1993
|View full text |Cite
|
Sign up to set email alerts
|

Recoverable and nonrecoverable deficits in conditioned responses after cerebellar cortical lesions

Abstract: This study reexamined the effects of unilateral damage to cerebellar hemispheral lobule VI on the rabbit's conditioned nictitating membrane (NM) response. Extensive unilateral removal of hemispheral lobule VI in 11 rabbits impaired ipsilateral conditioned responses as reflected by reductions of 52% in mean frequency and 53% in mean amplitude during test trials on the first postoperative session. The decreases in the amplitude and frequency of conditioned responses were highly correlated (r = 0.82). The frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
39
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 48 publications
(76 reference statements)
8
39
0
Order By: Relevance
“…compared with the modest effect observed in New Zealand White rabbits used in all other experiments (Clark and Lavond 1994). More recent data from Yeo and associates, however, suggest that the prelesion CR frequency is recoverable to some degree in Dutch belted rabbits with postlesion training, but that a concomitant decrease in CR amplitude does not recover with additional training (Harvey et al 1990;Yeo and Hardiman 1992;Gruart and Yeo 1995). The effects of HVI lesions on CR amplitude remain in dispute, although the converging evidence suggests that unilateral lesions minimally disrupt retention of the CR Lavond et al 1987;Clark et al 1990;Perrett and Mauk 1995).…”
Section: Hvi and Cr Acquisition And Expressionmentioning
confidence: 84%
See 1 more Smart Citation
“…compared with the modest effect observed in New Zealand White rabbits used in all other experiments (Clark and Lavond 1994). More recent data from Yeo and associates, however, suggest that the prelesion CR frequency is recoverable to some degree in Dutch belted rabbits with postlesion training, but that a concomitant decrease in CR amplitude does not recover with additional training (Harvey et al 1990;Yeo and Hardiman 1992;Gruart and Yeo 1995). The effects of HVI lesions on CR amplitude remain in dispute, although the converging evidence suggests that unilateral lesions minimally disrupt retention of the CR Lavond et al 1987;Clark et al 1990;Perrett and Mauk 1995).…”
Section: Hvi and Cr Acquisition And Expressionmentioning
confidence: 84%
“…Some of the earliest studies to target this region were performed by Yeo and colleagues, and the results suggested that selective lesions of HVI or HVI and the ansiform lobule completely block expression of the conditioned response in well trained animals (Yeo et al 1984(Yeo et al , 1985bHardiman et al 1988;Yeo and Hardiman 1988). Subsequent attempts to replicate this result have proven unsuccessful; however, even when the complex conditioning protocol used in the Yeo et al studies is employed Lavond et al 1987;Clark et al 1990;Harvey et al 1993;Perrett and Mauk 1995).…”
Section: Hvi and Cr Acquisition And Expressionmentioning
confidence: 99%
“…Finally, the results of the cortical-lesioned group deserve additional comment in this context since different results have been obtained and different interpretations have been offered for conditioning of the nictitating membrane when the cerebellar cortex has been lesioned (Clark & Lavond, 1994;Dersarkissian, Logan, & Thompson, 1995;Glickstein, 1992;Hardiman & Yeo, 1992;Harvey, Welsh, Yeo, & Romano, 1993). Given all of this information, we cannot conclude at the present time that the cerebellar cortex is not necessary for concurrent TAL and, on the contrary, it appears to meet the essential requirements for participating in the acquisition process, as can be deduced from anatomical, electrophysiological, and other behavioral studies (Black, Isaacs, Anderson, Alcantara, & Greenough, 1990;Kim & Thompson, 1997;Schreurs, Sanchez-Andres, & Alkon, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6 shows example photographs of the cerebellar cortex for saline and OX7-saporin rats. The moderate cell loss in the inferior olive associated with Purkinje cell depletion is also seen following cerebellar cortical lesions (Harvey et al, 1993;Lavond et al, 1987;Woodruff-Pak et al, 1993;Yeo et al, 1985) and in pcd mice (Chen, Bao, Lockard, Kim, & Thompson, 1996;Chen, Bao, & Thompson, 1999). Other components of the eyeblink conditioning circuitry, including the cochlear nuclei, pontine nuclei, red nucleus, facial motor nucleus, and deep nuclei (see below), were unaffected by OX7-saporin.…”
Section: General Histologymentioning
confidence: 94%